Optimizing Response Functions of Media Exposure Distributions - Danaher, Peter J. (The Journal of the Operational Research Society, 1991)
The object of this paper is to show how to maximize the expected response of an advertising campaign, subject to a budget constraint. Four response functions are considered with closed-form solutions given for the resulting expected responses. These expected responses use only univariate marginal distributions and pairwise duplications, so they can be rapidly calculated compared with the usual cumbersome calculation based on the full frequency distribution. A simple heuristic solution to the formulated non-linear integer programming problem is given, resulting in big savings in computation time over the branch-and-bound technique, for example.